THE USE OF PSYCHOLOGICAL TRAINING AND EXERCISES IN THE DEVELOPMENT OF LEADERSHIP SKILLS IN STUDENTS (Proceedings of International Educators Conference, 2024)
This article describes the effective methods of using psychological training and exercises in the formation of leadership skills in the student community.